Genome-wide identification, phylogeny, and expression analysis of pectin methylesterases reveal their major role in cotton fiber development. (December 2016) - Li, Weijie; Shang, Haihong; Ge, Qun; Zou, Changsong; Cai, Juan; Wang, Daojie; Fan, Senmiao; Zhang, Zhen; Deng, Xiaoying; Tan, Yunna; Song, Weiwu; Li, Pengtao; et al.
Abstract Background Pectin methylesterase (PME, EC 3.1.1.11) is a hydrolytic enzyme that utilizes pectin as substrates, and plays a significant role in regulating pectin reconstruction thereby regulating plant growth. Pectin is one of the important components of the plant cell wall, which forms the main structural material of cotton fiber. In this research, cotton genome information was used to identifyPMEs . Results We identified 80 (GaPME01 -GaPME80 )PME genes from diploidG. arboreum (A genome), 78 (GrPME01 -GrPME78 )PME genes fromG. raimondii (D genome), and 135 (GhPME001 -GhPME135 )PME genes from tetraploid cottonG. hirsutum (AD genome). We further analyzed their gene structure, conserved domain, gene expression, and systematic evolution to lay the foundation for deeper research on the function ofPMEs . Phylogenetic data indicated that members from the same species demonstrated relatively high sequence identities and genetic similarities. Analysis of gene structures showed that most of thePMEs genes had 2–3 exons, with a few having a variable number of exons from 4 to 6. There are nearly no differences in the gene structure ofPMEs among the three (two diploid and one tetraploid) cotton species. Selective pressure analysis showed that the Ka/Ks value for each of the three cotton speciesPME families was less than one. Conclusion Conserved domain analysis showed thatPMEs members had a relatively conserved C-terminal pectinesterase domain (PME) while the N-terminus was less conserved. Moreover, some of the family members contained a pectin methylesterase inhibitor (PMEI) domain. The Ka/Ks ratios suggested that the duplicatedPMEs underwent purifying selection after the duplication events. This study provided an important basis for further research on the functions of cottonPMEs . Results from qRT-PCR indicated that the expression level of differentPMEs at various fiber developmental stages was different. Moreover, some of thePMEs showed fiber predominant expression in secondary wall thickening indicating tissue-specific expression patterns.